2020
DOI: 10.1002/ldr.3719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frame beam on structural characteristics of artificial soil on railway cut‐slopes in southwestern China

Abstract: Cut-slope restoration technologies commonly used in southwest China mainly include using simple outside soil spray seeding (OSSS) techniques, or OSSS combined with an anchor frame beam. Artificial soil used in OSSS can establish a soil layer suitable for revegetation; the addition of an anchor frame beam not only fixes soil and shallow rock, it also acts to strengthen deep rock. However, there have been few studies on the effects of frame beams on artificial soil structural characteristics on railway cutslopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…On the other hand, the soil porosity in CSN and CST was higher than that in CSG. High porosity reduced soil aggregate stability against hydraulic erosion and mechanical stress (Ai, Sheng, et al, 2021; Ai, Wang, et al, 2021). Random Forest model analysis found that large macro‐aggregates was the largest contributing factor to soil aggregate stability (Figure S3), and the stability increased with the increase of the mass proportion of large macro‐aggregates, which was consistent with the previous research results (Abiven et al, 2009; Li, Wang, et al, 2021; Li, Li, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the soil porosity in CSN and CST was higher than that in CSG. High porosity reduced soil aggregate stability against hydraulic erosion and mechanical stress (Ai, Sheng, et al, 2021; Ai, Wang, et al, 2021). Random Forest model analysis found that large macro‐aggregates was the largest contributing factor to soil aggregate stability (Figure S3), and the stability increased with the increase of the mass proportion of large macro‐aggregates, which was consistent with the previous research results (Abiven et al, 2009; Li, Wang, et al, 2021; Li, Li, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Soil spray seeding has been widely used in these areas because of its strong adaptability and rapid effect (Jiang et al, 2021). This process generally consists of laying soil consolidation mesh on a cut slope, then fixing it with anchor bolts and rivets, and finally spraying artificial soil on it with special sprayers (Ai, Sheng, et al, 2021). The aforementioned artificial soil is usually a mixture of clay loam, humus, soluble fertilizer, water retaining agent, binder, and plant seeds in a certain proportions (Fu et al, 2018; Li, Zhang, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the lattice beam placed on the slope surface is a reinforced concrete frame beam structure, which is mainly made of concrete with a compressive strength of not less than 25 MPa (C25), the crosssectional area of the beams is not less than b × h = 250 mm × 300 mm, and the distance between the adjacent beams in both directions should be less than 4.0 m [10]. Since the successful application of lattice beams in highway slopes in the 1980s in China, the lattice beam slope anchorage system has been widely used for the reinforcement of various high and steep man-made slopes [11][12][13] or landslides [14,15] due to its light weight, flexibility, and good seismic performance [16][17][18][19][20]. Similar to the design of the traditional slope retaining structure, in addition to obtaining the parameters such as displacement, stress, strain, and FOS of the slope by numerical analysis [21][22][23], the design of the lattice beam slope anchorage system requires accurate calculation of the internal forces such as bending moment and shear force of the lattice beam.…”
Section: Introductionmentioning
confidence: 99%
“…However, restoring these slopes has long posed a challenge for ecological rehabilitation practitioners. Despite various innovative engineering techniques for restoration [4][5][6][7], these methods often lead to unnatural and unsustainable post-recovery vegetation [2]. A more effective approach lies in understanding spontaneous processes like diffusion, colonization, and succession, pivotal for rehabilitating disrupted sites [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%